Back to the Future? : A critical reflection on Neil Kearney’s mature systems of industrial relations perspective on the governance of outsourced apparel supply chains /: A critical reflection on Neil Kearney’s mature systems of industrial relations perspective on the governance of outsourced apparel supply chains. (November 2011) - (Writer on industrial relations), Miller, Douglas; (Research assistant), Turner, Simon; Grinter, Tom
No abstract available